Intravaginal progesterone device and/or temporary weaning on reproductive performance of anestrous crossbred Angus x Nelore cows - Vasconcelos, José Luiz Moraes [UNESP]; Sa Filho, Ocilon Gomes [UNESP]; Perez, Gabriela Campos [UNESP]; Nogueira Silva, Aydson Takiguchi [UNESP] (Elsevier B.V., 2009)
The objective of this experiment was to evaluate effects of treatments with intravaginal progesterone (N) device and/or 48 h temporary weaning (TW) on reproductive performance of postpartum anestrous crossbred Angus x Nelore cows, throughout the breeding season (BS). Anestrous cows (n = 296; 53 5 DPP, body condition score between 2.5 and 3.5, on a 1-5 scale) were assigned randomly to four treatments (2 x 2 factorial design): (1) Control Group (no treatment; n = 73); (2) TW Group (48 h TW beginning on day 0 of BS; n = 70); (3) P4 Group (Intravaginal P4 device between days -7 and 0 of BS; n = 73); and (4) P4+TW Group (Intravaginal P4 device between days -7 and 0 of BS followed by 48h TW; n=70). on day 0 of BS (when P4 devices were removed and TW was initiated), cows had their ovaries evaluated by ultrasonography aiming to evaluate size of the largest follicle. Signs of behavioral estrus were observed twice a day (morning and evening), between days 0 and 25 of BS, and cows observed in estrus were inseminated 12 h later. Between days 26 and 80 of BS, cows were submitted to natural service. Pregnancy diagnosis was conducted by transrectal ultrasonography on days 32 and 53 (pregnancies by AI) and 114 (pregnancies by natural service). Rates of detection of estrus during the first 3 days and within 25 days of BS were greater in cows receiving TW (45.0% compared with 9.6% and 50.0% compared with 29.5%, respectively; P < 0.01). Conception rate in cows inseminated in the first 3 days of BS was greater in cows treated with P4 (54.8% compared with 11.1 %; P < 0.01). Combining P4+TW increased pregnancy rate in the first 3 days (Control: 1.4%, TW: 4.3%, P4: 8.2% and P4+TW: 24.3%; P < 0.01) and in 25 days of BS (Control: 10.9%, TW: 7.1%, P4: 13.7% and P4+TW: 28.6%; P < 0.05). Pregnancy rate at the end of BS did not differ among treatment groups. In conclusion, TW alone increased estrous behavior whereas P4 alone benefited conception. Combining P4 with TW improved pregnancy rate with direct benefits to behavioral estrus and conception. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Beef cows; Temporary weaning; Anestrous; Progesterone